National Planetary Health learning objectives for Germany: A steppingstone for medical education to promote transformative change - Wabnitz, Katharina; Schwienhorst-Stich, Eva-Maria; Asbeck, Franziska; Fellmann, Cara Sophie; Gepp, Sophie; Leberl, Jana; Mezger, Nikolaus Christian Simon; Eichinger, Michael (Frontiers in Public Health, 2023)
Physicians play an important role in adapting to and mitigating the adverse health effects of the unfolding climate and ecological crises. To fully harness this potential, future physicians need to acquire knowledge, values, skills, and leadership attributes to care for patients presenting with environmental change-related conditions and to initiate and propel transformative change in healthcare and other sectors of society including, but not limited to, the decarbonization of healthcare systems, the transition to renewable energies and the transformation of transport and food systems. Despite the potential of Planetary Health Education (PHE) to support the development of knowledge, values, skills and leadership attributes in medical students, best-practice examples of mainstreaming PHE in medical curricula remain scarce both in Germany and internationally. The process of revising and updating the Medical Licensing Regulations and the National Competency-based Catalogue of Learning Objectives for Medical Education in Germany provided a window of opportunity to address this implementation challenge. In this article, we describe the development and content of national Planetary Health learning objectives for Germany. We anticipate that the learning objectives will stimulate the development and implementation of innovative Planetary Health teaching, learning and exam formats in medical schools and inform similar initiatives in other health professions. The availability of further PHE catalogues in other countries provides opportunities for cross-country and interdisciplinary exchange of experiences and validation of content, thus supporting the consolidation of Planetary Health learning objectives and the improvement of PHE for all health professionals globally.